Analisis Opini Audit Terhadap Kinerja Organisasi - Sunarmin Sunarmin (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
Financial Statement Audit is an audit conducted by an independent auditor of the financial statements presented by his client to express an opinion on the fairness of the financial statements. The audit report is a formal medium used by the auditor to communicate to interested parties about the conclusions of the audited financial statements. In issuing the audit report, the auditor must comply with the 4 reporting standards set forth in the generally accepted auditing standards.This analysis is a review of several sources, including from manuals, published studies, legislation published by state organizers as well as some information from media news. This analysis is much related to the phenomenon that has become a source of news in June 2017 and related to the role, function and benefits of the opinion audit conducted by external audit of the organization, both non-profit objectives and expanded to profit organizations. This analysis aims to be more convincing whether there is a significant influence on audit opinion on organizational performance.The result of this analysis can be concluded that, the existence of audit opinion from result of examination conducted by independent accountant, apparently have a very significant influence to the good performance for non-profit organization (government institution, community institution), or profit organization (public company).